Characterizing Antimicrobial Resistance in Chicken Pathogens: A Step towards Improved Antimicrobial Stewardship in Poultry Production in Vietnam - Nguyen Thi Phuong Yen; Nguyen Thi Nhung; Nguyen Thi Bich Van; Nguyen Van Cuong; Bach Tuan Kiet; Doan Hoang Phu; Vo Be Hien; James Campbell; Niwat Chansiripornchai; Guy E. Thwaites; Juan J. Carrique-Mas (MDPI AG, 2020)
In the Mekong Delta of Vietnam, farmers use large quantities of antimicrobials to raise small-scale chicken flocks, often including active ingredients regarded of "critical importance'" by the World Health Organization. Due to limitations in laboratory capacity, the choice of antimicrobials normally does not follow any empirical criteria of effectiveness. The aim of this study was to highlight non-critically important antimicrobials against which chicken pathogens are likely to be susceptible as a basis for treatment guidelines. Microtiter broth dilution method was performed to determine the minimal inhibitory concentration (MIC) of 12 commonly used antimicrobials for 58 isolates, including Ornithobacterium rhinotracheale (ORT) (n = 22), Gallibacterium anatis (n = 19), and Avibacterium endocarditidis (n = 17). Unfortunately, internationally accepted breakpoints for resistance in these organisms do not exist. We drew tentative epidemiological cut-offs (TECOFFs) for those antimicrobial-pathogen combinations where MIC distributions suggested the presence of a distinct non-wild-type population. Based on the observed results, doxycycline would be the drug of choice for A.endocarditidis (11.8% presumptive non-wild type) and G. anatis infections (5.3% presumptive non-wild type). A total of 13.6% ORT isolates were non-wild type with regards to oxytetracycline, making it the drug of choice against this pathogen. This study illustrates the challenges in interpreting susceptibility testing results and the need to establish internationally accepted breakpoints for veterinary pathogens.